2016
DOI: 10.5001/omj.2016.85
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Covariates of Polypharmacy in Elderly Patients on Discharge from a Tertiary Care Hospital in Oman

Abstract: The prevalence of polypharmacy among elderly medical patients discharged from our hospital was high (76.3%) and was associated with a number of comorbidities and cardiovascular disease as a cause of admission, but not with age or gender. The prevalence of polypharmacy in our institution raises significant concerns over its potential impact on patients' health outcomes and requires further investigation. Raising physicians' awareness of health implications of polypharmacy may help reduce the incidence of medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 25 publications
7
34
1
3
Order By: Relevance
“…Anti-infectious were also associated with polypharmacy due to the high prevalence of infectious diseases as reported previously [46]. These findings are similar to findings reported by previous studies that reported a high prevalence of administration of cardiovascular system drugs, drugs acting on blood and blood forming organ, alimentary tract and metabolism drugs and anti-infectious drugs [23,25,34,46].…”
Section: Association With Comorbidities and Drug Classificationsupporting
confidence: 82%
See 2 more Smart Citations
“…Anti-infectious were also associated with polypharmacy due to the high prevalence of infectious diseases as reported previously [46]. These findings are similar to findings reported by previous studies that reported a high prevalence of administration of cardiovascular system drugs, drugs acting on blood and blood forming organ, alimentary tract and metabolism drugs and anti-infectious drugs [23,25,34,46].…”
Section: Association With Comorbidities and Drug Classificationsupporting
confidence: 82%
“…Another study conducted in Dubai reported that 89% of the participated patients were taking more than five medications [29]. Our results were comparable to a study conducted in Oman on discharged geriatrics and reported polypharmacy in 76.3% of the participants [23].…”
Section: Prevalence Of Pddi and Polypharmacysupporting
confidence: 81%
See 1 more Smart Citation
“…This is comparable with the study done in Ayder referral hospital, Tigray, Ethiopia which showed that infection diseases were diagnosed in 58.6% of the study participant [20]. However according to the retrospective study done in Oman [6], more patients had CVD on admission (31%) followed by infection (23.0%) and GIT diseases (13%). This might be consistent with the possible reason that CVD are highly prevalent among higher income countries while infection is common among developing countries including Ethiopia.…”
Section: Discussionsupporting
confidence: 67%
“…There is no standard cut point with regard to the number of medications that is agreed up on for the definition of poly-pharmacy [5]. The definition of poly-pharmacy varies in the literature, but it ranges from the concurrent use of two or more to five or more prescription drugs [6]. However, it is mostly defined as the concurrent use of four or more prescription drugs [7,8].…”
Section: Introductionmentioning
confidence: 99%